IMPLEMENTASI PEMBELAJARAN MULTIPLE INTELLIGENCE DALAM KURIKULUM MERDEKA PADA SISWA DI SEKOLAH DASAR - Patras, Yuyun Elisabeth; Hidayatulloh, Muhamad Syarif; Agustin, Rizkha Halia (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
The purpose of this study is to describe the recommendations for learning Multiple Intelligence in the independent curriculum in elementary schools, these findings are then used as a basis to encourage the implementation of the learning process that uses multiple intelligence learning in elementary schools. The research method uses content analysis of 2019-2023 articles from Publish or Perish using Google Scholar data searched using the keywords "multiple intelligence learning , multiple intelligence learning strategies in independent curricula in elementary schools". Research findings show that multiple intelligence learning can be used in an independent curriculum and has an impact on the process of student learning success in school, a factor that influences student learning success both from increasing understanding, learning effectiveness, creativity skills owned by students. The recommendations for educational units in the learning process, namely the application of multiple intelligence learning in the independent curriculum must consider the characteristics, interests and needs of students in the learning process at school. The results of the study provide input for the application of multiple intelligence-based learning in elementary schools.